Las medidas de arraigo en los procedimientos coactivos y su vulneración al derecho de libre circulación - Delgado Casanova, Carlos Eugenio (2017)
This paper analyzes the violation of the free movement right as a consequence of the imposition of the prohibition measures to leave the country, which are ordered within the administrative procedures of coercive execution, which is incommensurate and unnecessary by the fact of subjecting one fundamental right for the fulfillment of a determined debt in favor of the State. In order to explain this fact, the development of the paper will be addressed by a doctrinal, legal and jurisprudential analysis regarding the legal nature of the coercive procedure as an element of the self-administrative protection principle, the debt collector competences, and the compatibility of this legal framework and its methods, with the free movement right as a fundamental right inherent to the human being and whose restriction is subject to the circumstances that are not adapted to current administrative enforcement procedures.